2013
DOI: 10.3389/fneur.2013.00068
|View full text |Cite
|
Sign up to set email alerts
|

The Serendipity Case of the Pedunculopontine Nucleus Low-Frequency Brain Stimulation: Chasing a Gait Response, Finding Sleep, and Cognition Improvement

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an efficacious therapy for Parkinson’s disease (PD) but its effects on non-motor facets may be detrimental. The low-frequency stimulation (LFS) of the pedunculopontine nucleus (PPN or the nucleus tegmenti pedunculopontini – PPTg-) opened new perspectives. In our hands, PPTg-LFS revealed a modest influence on gait but increased sleep quality and degree of attentiveness. At odds with potential adverse events following STN-DBS, executive functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 109 publications
1
32
0
Order By: Relevance
“…Surprisingly, however, numerous studies have described that patients often feel subjectively more “alert” upon the onset of low frequency (15-25Hz) DBS in the PPN (Stefani et al, 2013). Our data can provide a potential explanation for these findings, demonstrating that the MLR/PPN mediates both locomotion as well as changes in behavioral state that are naturally recruited in tandem.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, numerous studies have described that patients often feel subjectively more “alert” upon the onset of low frequency (15-25Hz) DBS in the PPN (Stefani et al, 2013). Our data can provide a potential explanation for these findings, demonstrating that the MLR/PPN mediates both locomotion as well as changes in behavioral state that are naturally recruited in tandem.…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated, patients commonly report a heightened feeling of alertness (Stefani et al 2013). It is plausible that alertness would be the subjective feeling associated with the high-gate state of cortex; however, we do not know whether locomotion induces a high-gain state in human visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Moro et al (2010) used unilateral stimulation at 50 Hz and 70 Hz, and showed improvements in falls and motor scores. Stefani et al (2007, 2013) used PPN stimulation at 10 Hz and 25 Hz, with some improvements in motor scores but a significant improvement in sleep patterns and modest improvement in gait. Alessandro et al (2010) using 25 Hz stimulation showed no motor improvements but significant amelioration in sleep scores and executive function.…”
Section: Implications For Dbsmentioning
confidence: 99%
“…Studies need to be performed to determine the effects of short- and long-term PPN DBS on cortical high frequency EEG activity. There is some information that PPN DBS may improve cognitive function (Tyckoki et al 2011), and that low frequency stimulation (5–30 Hz) may improve executive and higher functions (Stefani et al 2013), but this issue needs further elucidation. After all, lesions of the PPN disturb attention, executive function and working memory (Winn 2008).…”
Section: Suggestions For the Futurementioning
confidence: 99%